AN ANALYSIS OF DEIXIS IN THE KING’S MAN (2021) MOVIE: PRAGMATICS STUDY - Harfianto Martha Mustaqiem; Ervina CM Simatupang (JURNAL DARMA AGUNG, 2023)
The goal of this research is to identify the different types of deixis and the most dominant deixis in the Kings'man Movie. This study used a qualitative approach, with data gathered by watching the film and trancribing the dialogue delivered by the characters. The data used in this paper are the movie The King's Man and its transcript. This study looked into two research questions. The first question is to determine what types of deixis are found in The King's Man Movie, and the last is to determine the types of deixis that are most commonly used in The King's Man Movie. The researcher discovered 786 deixis data. The data was categorized to person, time, place, discourse, and social deixis. The result showed that there are 666 person deixis (85%), 14 time deixis(2%), 22 place deixis (3%), 52 discourse deixis(7%), and 32 social deixis( 4%). the most dominant types of deixis is person deixis.